Contemporary Indian Art : An Exhibition of the Festival of India, 1982. ([S.l.] : Indian Advisory Committee, Festival of India, U.K., 1982)
Bawa, Manjeet ; Bhattacharjee, Bikash ; Chhabda, Bal ; Chowdhury, Jogen ; Davierwalla, A.M. ; De, Biren ; Gaitonde, V.S. ; Goud, Laxma ; Gujral, Satish ; Husain, M.F. ; Kalka, Ranbir Singh ; Katt, Latika ; Khakhar, Bhupen ; etc.
Contemporary Indian Art : An Exhibition of the Festival of India, 1982, The Royal Academy of Arts, London, I. The Gesture, and Motif, 18th September to 5th October 1982 ; II. Stories, Situations, 9th October to 31st October 1982
boek
Keywords: India